Steering the medical maze beyond memorization: Harnessing the potential of open-book tests in medical learning - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Wolters Kluwer Medknow Publications, 2024)
In the field of medical education, we have employed the closed-book test format as the standard approach for carrying out assessments for many decades. An open-book test in medical education is an assessment method wherein medical students are permitted to refer to learning resources during the examination. Thus, students do not rely primarily on their memory and understanding of the subject rather can access external resources to supplement their problem-solving and decision-making abilities. Even though multiple merits have been attributed to open-book tests, we must give attention to the time duration and the kind of references students can access during such tests. At this juncture, we must reiterate that we are not advocating that open-book tests should be introduced and they should replace the conventional closed-book tests. However, there is immense scope for open-book tests in medical education, and every medical institution must explore the scope and feasibility to introduce open-book tests within their settings.